Comparison in the Effect of Resistance Punch and Dumbbell Punch Training Toward the Enhancement of Arm Muscle Power of Kyorugi Athletes of Ocean Taekwondo Club, Magelang Regency - Kristian Abimanyu, Indra; Tirtawirya, Devi (Indonesian Conditioning Coaches, 2025)
This study aims to investigate the effect of resistance punch training on arm muscle power, examine the effect of dumbbell punch training on arm muscle power, and determine whether there is a significant difference between the two training methods in developing arm power among kyorugi athletes of Ocean Taekwondo Club, Magelang Regency. This research employed a quantitative experimental approach using a two-group pretest–posttest design. A total of 20 athletes were selected through purposive sampling based on inclusion criteria such as training experience, belt rank, and age suitability. The participants were divided into two equal groups: a resistance punch training group and a dumbbell punch training group. Both groups underwent 16 training sessions, and arm muscle power was assessed using the medicine ball chest pass test. The results of the paired sample t-test revealed that resistance punch training had a significant effect on enhancing arm muscle power, indicated by a significance value of 0.03 (<0.05) with an improvement of 0.47%. Dumbbell punch training also produced a significant effect, with a significance value of 0.01 (<0.05) and an improvement of 0.58%. However, the independent sample t-test indicated no significant difference between the two training methods, with a significance value of 0.732 (>0.05). These results demonstrate that both training variations are effective in increasing arm muscle power, but neither method is superior. Overall, the study suggests that coaches may implement either resistance punch or dumbbell punch training as both are capable of improving arm muscle explosiveness essential for kyorugi performance. The findings may serve as a reference for designing upper-body power development programs tailored to combat sport athletes.